DSN-MUI Fatwa as a Source of Law in the National Sharia Economic Legal System - Mualim, Mualim; Mukhlas, Oyo Sunaryo; Hakim, Atang Abd. (Journal of Applied Business, Taxation and Economics Research, 2026)
The development of Islamic economic law in Indonesia is inseparable from the contribution of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), as a religious authority that issues fatwas on contemporary muamalah practices. DSN-MUI fatwas not only serve as normative guidelines for the operations of Islamic financial institutions but also serve as substantive references in the formation of national Islamic economic regulations. This article aims to examine the position and legal force of DSN-MUI fatwas in the Indonesian legal system, while also analyzing the mechanisms for transforming religious norms into positive law. This research uses a normative juridical approach with a qualitative-descriptive analysis method of laws and regulations, DSN-MUI fatwas, and court decisions related to Islamic economic disputes. The results show that DSN-MUI fatwas occupy a strategic position as a source of material law that provides a normative basis for the birth of regulations, such as Law Number 21 of 2008 concerning Islamic Banking and various Financial Services Authority Regulations. However, formally, fatwas do not have direct binding force before being adopted into laws and regulations. Therefore, strengthening the synergy between religious authorities and state institutions is an important prerequisite for realizing a national Islamic economic legal system that is integrated, responsive, and equitable.